Preparation of feed-grade monocalcium phosphate by crystallization in aqueous medium: Calculation and experiments - Bac, Nguyen Quang; Duc, Ta Hong (Vietnam Journal of Science and Technology, 2021)
In this paper, we present the results of calculation, and experiments for the preparation of feed-grade monocalcium phosphate by crystallization method in phosphoric acid solution. Some parameters influence to the production such as the reaction and crystallization temperature, the ratio of recycle mother liquor to reactant mixture have been investigated. The results show that the crystallization method in the preparation of monocalcium phosphate will give product with higher quality, less impurities that will be suitable for animal feed additives.